The influence of situational constraints on in-game penalty kicks in soccer - van Hemert, R.; van der Kamp, J.; Hartman, E. (International Journal of Performance Analysis in Sport, 2026)
This study examined the influence of situational constraints on professional soccer players` in-match penalty kick performance. Both pre-game and in-game situational constraints were considered. To this end, data on 7,199 penalty kicks from 5 European national leagues between 2008-2009 and 2021-2022 were collected. Hierarchal binary logistic regression analyses were conducted with nine situational factors to predict the kick outcome while controlling for three individual factors. The results revealed that penalty kicks were scored more often in the less prestigious league (Eredivisie). Furthermore, teams who were leading in the second half and players who observed a successful penalty kick from the opponent`s team scored their penalty kicks more often. Finally, players who scored a field goal earlier in the game scored less often. However, the explained variance of logistic regression models was small. The fact that players are hardly affected by situational constraints seems to indicate that there is a successful selection of who is going to take the penalty kick. The conclusion was supported by the supplemental finding that players who took more penalty kicks outperformed the other players. More research into the interplay of situational, individual, and task constraints is needed to predict the outcome of in-game penalty kicks better.